Partido Socialismo e Liberdade: divergências e convergência nas eleições de 2022 - Laguzzi, Vinícius Bachmann (Universidade Federal de São Carlos, 2023)
The present monographic work seeks to survey the history of PSOL, its main groupings, and objectives as a "Party," and its position regarding the 2022 presidential elections, which were marked by the dispute between Lula and Jair Bolsonaro. Formed by a rupture from the PT in 2003, PSOL has charted paths of distancing and approaches with the PT, and its internal currents have seen different strategies for strengthening its ranks and combating setbacks in recent years. The importance of PSOL to politics in Brazil is directly related to the defense of socialism as an alternative. According to Alencar (2018), socialism is not just a utopia or a dream but a historical and political necessity in the face of the social and environmental degradation produced by capitalism. For the same author, this alternative is possible and feasible for the 21st century, as it takes into account the demands and aspirations of social movements, workers, and minorities (ALENCAR, 2018). That said, we will seek to present these respective internal currents and their disputes and explain the transformations of the Party that accompanied the changes in Brazil itself, especially in the period after the parliamentary coup against Dilma Rousseff, the election of Bolsonaro, the pandemic, and the struggle to remove Bolsonaro from the presidency.
Partido Socialism and Liberty: divergences and convergences in the 2022 elections
Keywords: PSOL; Socialismo; Eleições; Socialism; Elections; PSOL; CIENCIAS HUMANAS